2023
DOI: 10.3389/fbioe.2023.1093926
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in antibacterial coatings for orthodontic appliances

Abstract: In the process of orthodontic treatment, the presence of orthodontic appliances makes it difficult to clean tooth surfaces. This can lead to an increased level of bacterial colonization, resulting in enamel demineralization and periodontal diseases. Considering the large surface area that orthodontic appliances usually have and that they can be in direct contact with bacteria throughout the treatment, modifications in the form of coatings on the surface of orthodontic appliances can be an effective and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It has been reported that the current enamel remineralization therapies have limited effects on post-orthodontic WSLs, and also heavily rely on the patients' compliance (Hu et al, 2020;Hua et al, 2020;Hua et al, 2018). Bacterial control modification of the dental appliances, on the contrary, doesn't require patient compliance and is gradually becoming an exciting notion for the prevention of the WSLs (Wang et al, 2023). To prevent the formation of enamel WSLs from an antimicrobial perspective, the novel attachment resin was formulated to contain antibacterial agents in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the current enamel remineralization therapies have limited effects on post-orthodontic WSLs, and also heavily rely on the patients' compliance (Hu et al, 2020;Hua et al, 2020;Hua et al, 2018). Bacterial control modification of the dental appliances, on the contrary, doesn't require patient compliance and is gradually becoming an exciting notion for the prevention of the WSLs (Wang et al, 2023). To prevent the formation of enamel WSLs from an antimicrobial perspective, the novel attachment resin was formulated to contain antibacterial agents in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These methods require patient cooperation, which is usually unpredictable. [ 124 ] Graphen-based materials with unique properties can be incorporated into orthodontic adhesives to improve their biological and mechanical properties. The addition of graphene-based materials to orthodontic adhesive was investigated in many studies.…”
Section: Potential Application Of Graphene-based Materials In Orthodo...mentioning
confidence: 99%
“…However, the use of orthodontic appliances, composed of archwires, brackets, and microimplants, presents a notable challenge in infection control due to the environment conducive to bacterial adhesion and biofilm formation [ 1 ]. Biofilm formation with increased levels of bacterial colonization on fixed orthodontic appliances poses significant risks to oral health, including dental caries, gingival inflammation, white spot lesions, and periodontal disease [ 2 ]. Plaque index values during orthodontic treatment were reportedly significantly higher than in the control group [ 3 ].…”
Section: Introductionmentioning
confidence: 99%